Possibilidade de atuação docente sobre o bullying nos anos iniciais - Santos, Stephanne Cavalcante dos (Universidade Federal de São Carlos, 2015)
This undergraduate thesis has as its object the teaching performance on bullying in the early years. The theme arose from the author's concern when she worked as an intern in the early years of Elementary School I in a public school in Sorocaba, São Paulo. With the experiences during the internships, the lack of teacher preparation in relation to bullying practices generated distress. The research seeks to understand how teachers who work in this segment perceive and forward the manifestations of bullying, analyzing how education professionals deal with such cases. The work is divided into three chapters. Chapter I presents the theoretical framework that supports the theme. This chapter begins with the excerpt called “School violence and bullying”, based on the studies of the Multifunctional Association for Support to Children and Adolescents (ABRAPIA), Lopes Neto (2005), Fante (2005), Oliboni (2008) and Pinheiro (2006). The second excerpt of the first chapter contains the “Concept of bullying” based on Fante (2005), Lopes Neto and Saavedra (2003), Olweus (1998; 1999), Lopes (2005) and Silva (2010). The third excerpt addresses the “Characteristics of bullying” and is based on Fante (2005), Lopes Neto (2005), Oliboni (2008) and Silva (2010). The fourth part presents the “History of bullying”, based on Lopes Neto and Saavedra (2003); Fante (2005) and Silva (2010). The fifth segment deals with “Studies and findings on bullying in Brazil” based on theoretical research carried out by the Multifunctional Association for Support to Children and Adolescents (ABRAPIA) and Fante (2005). Chapter II describes the methodology used to build the study, which is classified as qualitative and case study. To collect data, interviews were conducted with five teachers who work in the early years of Elementary School I in the city of Sorocaba. In Chapter III the data analysis is presented, interweaving the expressions of the teachers in the interviews with the theoretical references that support the work.
Possibilities of teaching actions about bullying on elementary school
Keywords: Bullying; Escola; School; Formação de professores; Teacher preparation; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO